Studi In Silico Prediksi Sifat Fisikokimia dan Toksisitas Senyawa Tectoquinone Sebagai α-Glukosidase inhibitor - Najib, Ahmad (Makassar Natural Product Journal (MNPJ), 2024)
Tectoquinone is a chemical compound from natural ingredients in the Syzigium oblanceolatum (C.B.Rob) plant. Previous research has proven that Tectoquinone has antidiabetic activity by inhibiting the α-glucosidase enzyme. This research on physicochemistry and toxicity aims to determine the feasibility of tectoquinone if used as an oral drug in silico using the pKCSM Online Tool. The results obtained are that tectoquinone has fulfilled the physicochemical test with parameters based on the Lipinski Rule of Five. However, the results of the toxicity test showed that tectoquinone had ames toxicity, hepatotoxicity, and the LD50 value obtained was 468.92 g/kg.